Intelligent Logistics Management in Industry 4.0: An Application Based on an Automated Intelligent Vehicle - Menezes, César (2019)
Companies that faces transport challenges and require logistics efficiency need to implement solutions based on automation, provided in Industry 4.0. Intelligent Logistics Management, satisfying the demanding requirements of the customer, using new technologies and advanced tools to control and to act along the supply chain are mandatory. To address this topic, this paper presents an application of an Automated Intelligent Vehicle.